What should global mental health do about violent extremism?. (2019) - Weine, S.; Kansal, S.
Abstract : To prevent radicalization to violence and to rehabilitate returned foreign terrorist fighters, new programs which go by the name of 'preventing and countering violent extremism' are being implemented globally, including in low- and middle-income countries. In some of these countries, global mental health strategies are also being implemented so as to deliver mental health care or psychosocial support to individuals and populations in need. This commentary addresses what global mental health should considering doing about violent extremism. Global mental health should be open to addressing the challenges of violent extremism but should do so based upon existing mental health and public health values, practices, and evidence. Global mental health could help by critically appraising preventing and countering violent extremism practices and by working with multidisciplinary stakeholders to develop new evidence-based and best practice models that are rooted in civil society ownership, community collaboration, broader prevention programing, and non-securitized approaches.